2019
DOI: 10.3390/ma12172837
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water on the Dynamic Tensile Mechanical Properties of Calcium Silicate Hydrate: Based on Molecular Dynamics Simulation

Abstract: To study the effect of water on the dynamic mechanical properties of calcium silicate hydrate (C–S–H) at the atomic scale, the molecular dynamics simulations were performed in uniaxial tension with different strain rates for C–S–H with a degree of saturation from 0% to 100%. Our calculations demonstrate that the dynamic tensile mechanical properties of C–S–H decrease with increasing water content and increase with increasing strain rates. With an increase in the degree of saturation, the strain rate sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 43 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…Shen and Xu [22] were in favor that the increase of porosity enhanced the impact of moisture content on strength, proposing a strength-porosity-saturation model based on the Ryshkewitch [23] model. By molecular dynamics simulation, Zhou and Liang [24] concluded that due to water molecular entering the C-S-H structure, the interatomic distance was entrenched, and atomic interactions were weakened.…”
Section: Introductionmentioning
confidence: 99%
“…Shen and Xu [22] were in favor that the increase of porosity enhanced the impact of moisture content on strength, proposing a strength-porosity-saturation model based on the Ryshkewitch [23] model. By molecular dynamics simulation, Zhou and Liang [24] concluded that due to water molecular entering the C-S-H structure, the interatomic distance was entrenched, and atomic interactions were weakened.…”
Section: Introductionmentioning
confidence: 99%
“… 52 , 53 It is reported that the tensile strengths of pure tobermorite are 2.03 and 2.41 GPa under the tensile strain rates of 1×10 8 and 1×10 9 s −1 , respectively; the tensile moduli of tobermorite are 40.11 and 42.05 GPa under the tensile strain rates of 1×10 8 and 1×10 9 s −1 , respectively. 51 The shear moduli of the BNNS-tobermorite composite are 70.1 ± 3.7 and 73.5 ± 1.8 GPa under the shear strain rates of 1×10 8 and 1×10 9 s −1 , respectively. 7 In view of the insensitivity of mechanical properties of tobermorite-based materials to the low strain rate ranging from 1×10 8 to 1×10 9 s −1 , the strain rate of 1×10 9 s −1 is adopted in the shear tests and the tensile test in MD simulations.…”
Section: Introductionmentioning
confidence: 90%
“…The mechanical properties of the tobermorite-based material are significantly dependent on the strain rate in MD simulations. For example, the high strain rate results in high mechanical properties of the tobermorite-based material because the material is damaged evenly at several locations, which requires high external work to be done to overcome the interaction between atoms, 51 while the low strain rate has limited influence on the mechanical properties of tobermorite-based materials. 52 , 53 It is reported that the tensile strengths of pure tobermorite are 2.03 and 2.41 GPa under the tensile strain rates of 1×10 8 and 1×10 9 s −1 , respectively; the tensile moduli of tobermorite are 40.11 and 42.05 GPa under the tensile strain rates of 1×10 8 and 1×10 9 s −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…As with other inorganic materials, the mechanical properties of calcite are affected by temperature and strain rate [54,55]. In order to study the effect of temperature on the deformation behavior, the strain rate was fixed at 1 × 10 8 s −1 but the temperature was changed from 10 K to 100 K, 200 K, 300 K, 400 K, and 500 K. Figure 11 shows the variations of fracture strength, fracture strain, and elastic modulus with temperature along the [010] , [421] , and [42 1] directions.…”
Section: Influence Of Temperature and Strain Ratementioning
confidence: 99%